A Cross-Sectional Study of Oral Lichen Planus Associated With Thyroid Diseases in East China - Tang, Yunju; Shi, Linjun; Jiang, Boren; Zhou, Zengtong; Shen, Xuemin (Frontiers in Endocrinology, 2020)
Objective: To investigate the prevalence of thyroid diseases in patients with oral lichen planus (OLP) and to explore the correlation between the two diseases. Methods: A cross-sectional study was conducted to investigate the history of thyroid disease in 585 patients with oral lichen planus diagnosed in the Department of Oral Mucosal Diseases of the Ninth People's Hospital, Shanghai Jiaotong University, School of Medicine from June 2017 to April 2018. Personal medical history of thyroid disease was obtained through questionnaire and thyroid function was also tested. Results: Of the 585 patients with OLP, 190 (32.48%) had thyroid disease (excluding coexistence of multiple thyroid diseases),62 (32.6%) had thyroid nodules, and 71(37.4%) had Hashimoto's thyroiditis. Hyperthyroidism was diagnosed in 6 patients (3.2%), hypothyroidism in 7 patients (3.7%), and thyroid cancer in 11 patients (5.8%). The prevalence of Hashimoto's thyroiditis was significantly higher in patients with oral lichen planus than in the general population. The probability of thyroid disease was significantly higher in women with OLP than in men with OLP (P<0.001). Conclusion: OLP is associated with a high probability of developing thyroid disease, especially Hashimoto's thyroiditis. In the management of OLP patients, especially in female patients, thyroid disease must be screened.